Tetrahydrofuran Ring Construction through Tandem Iodocyclizations: Synthesis of Hagen’s Gland Lactones, a Pheromone of Idea leuconoe, an Oxylipid, and Related Compounds - Nookaraju, U.; Danve, Shivam S.; Kumar, Pradeep (Synlett, 2025)
A simple and efficient common route was developed for the syntheses of tetrahydrofuran-ring-containing natural products such as Hagen’s gland lactones and their epimers, a pheromone of the butterfly Idea leuconoe, an oxylipid, and some valuable synthons. Brown’s allylation, cross-metathesis, iodocyclization, and a tandem aminoxylation/allylation were employed as key steps in the syntheses.
Keywords: tetrahydrofurans; iodocyclization; Hagen’s gland lactone; oxylipids; pheromones; cross-metathesis